Secondary renal amyloidosis in a 13-year-old girl with bronchiectasis - Eun Ae Yang; Dong Won Lee; Myung Chul Hyun; Min Hyun Cho (Korean Pediatric Society, 2010)
A 13-year-old girl was diagnosed with non-cystic fibrosis (CF)-related multifocal bronchiectasis accompanied by nephrotic-range proteinuria of unknown cause. On renal biopsy, there were many segmental homogeneous deposits of amyloid tissue with positive Congo red staining in the glomeruli and interstitium. On electron microscopy, relatively straight, non-branching, randomly arranged amyloid fibrils were showed in the mesangium of the glomeruli. These fibrils were approximately 10 nm in diameter, compatible with secondary amyloidosis. Her level of serum amyloid A was remarkably elevated. To our knowledge, this girl is the first case of secondary renal amyloidosis induced by bronchiectasis in Korean children.